(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The article is devoted to the evaluation of the role and advantages of the comparative method in the structure of social and humanitarian studies. The authors have revealed the peculiarity of the comparative method in the context of cultural and social objects and phenomena. The main problems of the comparative analysis in the framework of the dialogue between the cultures of the East and the West, the «connection» of their mental experience, the development of the practice of communication and mutual understanding, as well as the transformation in assessing the philosophical systems of East and West are noted in the article. The article notes the limits of applicability of comparative studies in the cultural sphere, as well as their prospects. The authors of the article draw a conclusion about the practical tasks and goals of the comparative approach in the cognitive and scientific fields, as well as in the social and cultural fields. Key words: comparativistics, philosophical comparativistics, culture, civilization, methodology, values, identity, dialogue of cultures, modernization, spirituality, consciousness.